Respuesta :
Answer:
Midpoint formula= [(x2+x1)/2],[(y2+y1)/2]
(4,-1)
StepByStep Explanation:
X , Y
((-2+10)/2) , ((-5+3)/2)
(8/2) , (-2/2)
4 , -1
=(4,-1)
For this case, we have to give two points of the form:
[tex](x_ {1}, y_ {1}) and (x_ {2}, y_ {2}})[/tex]
The formula of the midpoint is given by:
[tex](\frac {x_ {1} + x {2}} {2}, \frac {y_ {1} + y_ {2}} {2})[/tex]
So, be:
(10,3) and (-2, -5)
Substituting in the formula we have:
[tex](\frac {10 + (- 2)} {2}, \frac {3 + (- 5)} {2}) =\\(\frac {10-2} {2}, \frac {3-5} {2}) =[/tex]
Different signs are subtracted and the greater sign is placed:
[tex](\frac {8} {2}, \frac {-2} {2}) =[/tex]
(4, -1)
Thus, the midpoint is (4, -1)
Answer:
(4, -1)